Arthritis RX [videorecording (DVD)] : exercises to keep you active and pain free - Schultz, Ernie; Vad, Vijay; Culen, Stephanie (RLJ Entertainment, 2013)
Sports medicine specialist Vijay Vad, M.D., created these exercise programs to help you reduce pain, enhance mobility, and decrease your dependence on medication, regardless of your current fitness level. Arthritis Rx includes three levels of workouts based on yoga and pilates and is led by expert instructor Stephanie Culen. The beginners program helps increase your flexibility/ The intermediate exercises build strength, and the advanced ;eve; improves your endurance. Vad provides a step by step tutorial for each exercise so you can have complete confidence in their effectiveness. Get the active lifestyle you want with Arthritis RX.